(untitled) (Trinity Journal of Management, IT & Media (TJMITM), 2012)
The presence of mounting Non Performing Assets in the Indian banking system acts as a threat to their financial performance in several ways. Due to its increasing number earning assets in the financial sector decline even as operating expenses increases. Management and financial resources are diverted to Non Performing Assets problems and away from more productive uses. Non Performing Assets not only puts strain on the profitability on the banks but also eroded their productivity and efficiency. The Non Performing Assets are the bad debts and non recovered loans of the banks which now stand at over 90,000 crores. Large scale Non Performing Assets (NPA) when left unattended, causes continued economic and financial degradation. This results in credit crunch and generally signals adverse investment climate. To resolve NPA problems and help restore the health and confidence of the financial sector the Narshimham committee report (II) on banking sector reforms recommended the establishment of Asset Reconstruction Companies (ARC) and consequently, Asset Reconstruction Company Limited (ARCIL), the pioneer Assets Reconstruction of India, commenced its operation from August 29, 2003. This paper traces the various aspects like causes and impact of increasing NPA of Indian Banks along with the step forward taken by the ARCILin their restructuring.